2017
DOI: 10.1038/hdy.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversity and strong population structure shaped by anthropogenic habitat fragmentation in a critically endangered primate, Trachypithecus leucocephalus

Abstract: Habitat fragmentation may strongly impact population genetic structure and reduce the genetic diversity and viability of small and isolated populations. The white-headed langur (Trachypithecus leucocephalus) is a critically endangered primate species living in a highly fragmented and human-modified habitat in southern China. We examined the population genetic structure and genetic diversity of the species and investigated the environmental and anthropogenic factors that may have shaped its population structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 77 publications
(74 reference statements)
2
37
0
Order By: Relevance
“…The FS and CZ areas are separated by 40–50 km of flat area containing farmlands, roads, and villages. Previous population genetic analyses indicate high levels of genetic differentiation and very low levels of gene flow between the FS and CZ populations, suggesting genetic isolation, and demographic independence (Wang et al, ). Therefore, we analyzed the FS and CZ populations separately in the genetic analyses reported in this study.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The FS and CZ areas are separated by 40–50 km of flat area containing farmlands, roads, and villages. Previous population genetic analyses indicate high levels of genetic differentiation and very low levels of gene flow between the FS and CZ populations, suggesting genetic isolation, and demographic independence (Wang et al, ). Therefore, we analyzed the FS and CZ populations separately in the genetic analyses reported in this study.…”
Section: Methodsmentioning
confidence: 95%
“…A detailed description of the genetic diversity parameters of the microsatellite loci was reported previously (Wang et al, ). Genotyping data are available online (Dryad entry DOI will be provided later).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, increased levels of inbreeding and loss of genetic diversity threaten long‐term population survival and may lead to population extinction through decreased fertility, reduced ability to adapt to environmental changes, and enhanced susceptibility to infectious disease (Evans & Sheldon, ; Keller & Waller, ; O'Grady et al, ; Smith, Sax, & Lafferty, ; Willi, Van Buskirk, & Hoffmann, ). Threatened populations are frequently impacted by a multitude of factors starting with small long‐term effective population size (Abascal et al, ; Xue et al, ), low genetic diversity, habitat fragmentation and loss (Bergl, Bradley, Nsubuga, & Vigilant, ; Casas‐Marce, Soriano, López‐Bao, & Godoy, ), and other anthropogenic pressures (Brown, Peacock, & Ritchie, ; Wang, Qiao, Li, Pan, & Yao, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, geographic distance and fragmented habitat are often said to be barriers to allowing gene flow to occur and result in a lack of shared haplotype numbers, with many unique haplotypes restricted to single localities [Whitlock and McCauley, 1999;Warren et al, 2001;Ogata and Seino, 2015;Wang et al, 2017]. The current study showed only 8 haplotypes defined by 10 segregating sites from 1,434 bp.…”
Section: Gene Flow and Population Genetic Structurementioning
confidence: 88%